Mother Groups in the Faroe Islands: A qualitative study of how mothers experience participating in mother groups organized by visiting nurses - Sólja Oyvindardóttir av Skarði 1991- (2022)
This 60 credits master’s thesis in folkloristics/ethnology is a qualitative study of mother groups in the Faroe Islands. The thesis is built on 13 in-depth interviews with 12 mothers and 2 visiting nurses in addition to participant observations at 4 mother group meetings (with 3 different groups). The focus of the thesis is on how mothers experience taking part in the mother groups organized by visiting nurses, and which role the groups play in the mothers’ lives during the period after giving birth. Findings reveal that the mother groups are much valued among the women who take part in these groups and that they counteract the feeling of loneliness and social isolation, which are common amongst mothers on maternity leave. It takes time to learn to navigate life anew with a newborn family member, and many mothers expressed gratitude towards their mother group in this context. With the other mothers, they were able to talk about and share their thoughts and worries as well as the babies’ milestones, which are topics they feel other people are not as excited to talk about or listen to. How personal and deep the conversations got varied from group to group. However, hosting a mother group can be stressful, and especially the breakfast table becomes enormous in some mother groups. The visiting nurses do, however, try to remind the mothers that hosting a mother group should not become a stress factor and provide the mothers with some tips on how they can host mother groups while keeping them simple. In this study special emphasis is placed on the breakfast table, an important scene that brings into perspective the very different perceptions and feelings that surround the mother group situation.